(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
There is a multitude of definitions of artificial intelligence (AI). The paper aims to provide keys of interpretation and a set of comprehensible definitions of AI, which are then utilized in multiple sub-fields of technology applications such as healthcare, education, security and defense. The analysis starts from providing a definition of the constituent elements of AI technology: Data, Big Data, Cloud, Algorithm and Machine Learning. The application of AI will also involve changes of a cultural and behavioral nature. These effects make it even more important to understand the impact that AI may have in technological, sociological, political and legal fields.